The role of the immune system in the generation of neuropathic pain. - Calvo, M; Dawes, J; Bennett, D (2012)
Persistent pain is a sequela of several neurological conditions with a primary immune basis, such as Guillain-Barré syndrome and multiple sclerosis. Additionally, diverse forms of injury to the peripheral or the central nervous systems--whether traumatic, metabolic, or toxic--result in substantial recruitment and activation of immune cells. This response involves the innate immune system, but evidence also exists of T-lymphocyte recruitment, and in some patient cohorts antibodies to neuronal antigens have been reported. Mediators released by immune cells, such as cytokines, sensitise nociceptive signalling in the peripheral and central nervous systems. Preclinical data suggest an immune pathogenesis of neuropathic pain, but clinical evidence of a central role of the immune system is less clear. An important challenge for the future is to establish to what extent this immune response initiates or maintains neuropathic pain in patients and thus whether it is amenable to therapy.